Deportation or Forgiveness in Hosea 1.6?: Verb Valence Patterns and Translation Proposals - Dyk, J. W. (The Bible translator, 2014)
In order to render a verb consistently within the syntactic pattern in which it occurs, it is necessary to take into account the presence of a direct object (one, multiple, or none), the possibility of an idiomatic expression involving the direct object, the lexical characteristics of the elements in the construction, and the presence and particular function of prepositions in relation to the verb. Lexicons often provide a broad range of meanings for a single verb, but because a pattern might be affected by the combination with other elements, it is not always clear under which conditions a specific significance is applicable. Exegetes and translators sometimes take the liberty of choosing rather freely from the offered dictionary glosses, apparently not being sufficiently aware that elements present in the context could pose restrictions on the choice of rendering. Using examples containing the Hebrew verbs עשׂה, נשׂא, and שׂים, the significance of the specific patterns in which these verbs occur is explored. Variety in the translations of these verbs is presented and analyzed. The insights inform a procedure for identifying the signification of Hebrew verbs in which a series of questions guides one to a consistent rendering of the pattern in which the verb occurs.